Методы автоматизированного анализа криомикроскопических препаратов - Аврунін, О. Г.; Сун, Х.; Глассмахер, Б. (ХНУРЭ, 2011)
Designing of algorithm and the special software for automatically analysis of cryomicroscopical probes. Stages of digital image processing of cryomicroscopical probes of endothelial cells are described. The main of these stages are: preprocessing of digital images of cryomicroscopical probes for noise reductions; gradient contour segmentation and filing area of cells, logical filtration for reduce artifacts from probe coloration and ice crystals, marking of founded images of microobjects and computation square and volume of the cells. Designing methods for monitoring of cells volume valuations before, in - and after frizzing process are proposed and discussed. Perspectives for methods and software for automatically analysis of several kinds of cells in frizzing process are discussed.
Keywords: биологическая структура; анализ биомедицинских изображений